Going beyond the pitch the impact of media organizations, and sponsors on the popularity of football in the Philippines - Quilloy, Sarah Eres 1990-; Topular, Maricar Tagle 1990-. (2012.)
"This study seeks to explain the role of media organizations and sponsors as advocate for sports development and their contribution to the popularity of football. In line with this, the researchers seek to a) find out the current media attention given by the media organizations, ABS-CBN Sports, AKTV, to local football, b)describe the role of the networks and the local football organizations, Philippine Football Federation (PFF) and United Football League-Football Alliance (UFL-FA), in airing of football games, c)know the marketing and media strategies employed by the PFF and UFL-FA, d) find out how the sponsors support local football teams, determine the current status of football in the Philippines, e) document the cases where the media organizations' football coverage contributed to the popularity of football, and f) ascertain the perception of audiences on local football. Defleur and Rockeach's Dependency Model and Boyle and Hayne's Sporting Triangle guided the researchers in establishing the relationshio existing among the sectors concerned. In order to find out the relationship existing among media organizations, sponsors and football organizations, the researchers conducted focus interviews. From each organization, the researchers interviewed the following: management and commentators from local media organizations, media and marketing officers and management (team managers, technical director, legal counsel) from local football organizations, and sponsors (Kia Philippines and Healthway). For the audiences' part, focus group discussion and focus interviews were employed. The study revealed that, the media, in general, contribute to the popularity of local football. With its popularity and the attention it received from the media, sponsors began supporting local football. In turn, the sponsors' support keeps the football organizations and clubs running. The sponsors further spearheaded the development of football programs.Lastly, the audiences, as spectators, were drawn to football out of curiosity and support for the national team but their interest in local football is still mainly grounded to the Philippine Azkals and its players."
Vita.
Thesis (A. B. in Journalism)--University of the Philippines, Diliman.
Keywords: Mass media and sports; Football -- Philippines -- Press coverage